Participatory modeling and analysis of sustainable forest management: experiences and lessons learned from case studies - Mendoza, G.A.; Prabhu, Ravi (United States Department of Agriculture, 2005)
Participatory approaches to natural resource management and development have become widely accepted as the most effective instruments for achieving sustainable resource management particularly in the developing nations. This paper presents a participatory modeling framework that is consistent with participatory method of assessing sustainable forest management. Under this participatory modeling framework, a number of techniques have been developed aimed at: 1) communicating the concept of sustainable forestry to local communities, 2) soliciting direct input and active participation of local communities in the planning and decision-making process, and 3) seeking active involvement of local stakeholders in the formulation of the models and in their implementation for generating strategies and action plans. These models include: multi-criteria analysis, cognitive mapping, qualitative, and quantitative system dynamics. The models can be stand-alone models, or they can be combined together to constitute a more robust and flexible planning framework. These models have been applied to a number of case studies in the Philippines, Indonesia, Zimbabwe, and Ontario, Canada. Experiences and lessons learned from a selected set of applications are described in the paper.